THE USE OF ENGLISH CHILDREN SHORT STORY TO ENRICH STUDENTS' VOCABULARY ACHIEVEMENT AT FIRST GRADE OF STUDENT SMAN 2 SUBANG (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
In today's era, the use of English is needed to communicate with people at home and abroad. That way learning English is very important for us, because it makes it easier for us to communicate with people in the world. English as a foreign language has four skills. They speak, listen, write and read. This means that listening, speaking, reading and writing require mastery of a broad vocabulary. Vocabulary mastery is an important part of learning a foreign language. Communication will be successful or not depending on the accurate understanding of vocabulary. Where in learning English students cannot listen, speak, read and write well if they do not know vocabulary and one word correctly
Keywords: Vocabullary; Reading